The crystal structure of 2-amino-4-carboxypyridin-1-ium perchlorate, C6H7ClN2O6 - Zhang Tao; Luo Yingchun; Hu Hailiang (Zeitschrift für Kristallographie - New Crystal Structures)
C6H7ClN2O6, triclinic, P1̄ (no. 2), a = 5.3033(6) Å, b = 8.8875(10) Å, c = 10.3403(12) Å, α = 73.427(10)° $73.427(10){}^{°}$ , β = 85.158(10)°, γ = 73.284(10)°, V = 447.38(9) Å3, Z = 2, R gt(F) = 0.0370, wR ref(F 2) = 0.0900, T = 292.99(10) K.